TINJAUAN HUKUM PEMBUKTIAN DIGITAL SIGNATURE DITINJAU DARI UU NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Putri, Eka Aulia; Marilang; Natsif, Fadli Andi; Istiqamah; Nurjannah, St. (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2026)
The main problem in this study is how the requirements for digital signatures can be recognized as valid evidence, and how the legal strength of digital signature evidence is reviewed from Law concerning information and electronic transactions. Research type is library research with a juridical-normative approach. The results of this research obtained by the author are the digital signature requirements so that they can be recognized as valid evidence, in article 11 of the ITE Law which stipulates that. The legal strength of proof inherent in digital signatures in terms of civil evidence has the legal power of evidence at the same level as private certificates, therefore the legal strength of evidence inherent in signatures on electronic letters is only formal and material proof.